NOWE PRAWO WŁASNOŚCI – PRZEKSZTAŁCENIA W STOSUNKACH WŁASNOŚCIOWYCH W POLSCE W LATACH 1944-1950 - Machnikowska, Anna (Zeszyty Prawnicze, 2016)
NEW PROPRIETORSHIP – PRIVATIZATION TRANSFORMATIONS IN POLAND IN YEARS 1944-1950 Summary In the first years of the People’s Republic of Poland a partial change in the contents and the function of proprietorship occurred. The modification, in which the majority of the society believed for a long time, meant not only the introduction of new subjects under a given proprietorship, but also a real re-definition of the very notion of ownership. Then, shifts in restrictions imposed on proprietorship occurred. Before they were placed besides law, among other things in administrative regulations; as a result of the new solutions they have directly been included in proprietorship. This led to proportion changes between the rights and duties of owners and non-owners. Civil law tradition was abandoned, although it did not treat proprietorship as absolute law, but it did not impose any concreto limits. Civil law tradition accepted the assumption that the possible unlimited freedom of the proprietor connected with law’s flexibility is the characteristic feature of proprietorship. It proved that restrictions did not constitute the essence of ownership and they had a different role in it. Hence, it was underlined that the possible narrowing of the owner’s rights should have short-termed and individual character, established according to the law. Yet, the new transformations of proprietorship accepted a different assumption. The characteristic feature was that they were not distinctly visible and recognizable in the first years. They were not expressed in the theory of law while the thesis was developed in the sphere of politics and propaganda that its aim was to make proprietorship more wide spread and to enhance its social function. The political idea of proprietorship management appeared after many attempts taken up at the turn of the 40s and 50s. The referred theory of law was rather a false justification than the real, essential foundation of taken up activities at that time, as the new authorities did not manage to elaborate a coherent concept of socialist proprietorship fulfilling civil law criteria, even with the help of the Soviet achievements. Due to this reason slogans were mainly used, which were to signify the conformity of practice with the declaration of nationalization. In fact, they concentrated on the current property administration, property either taken over or controlled by the state. It was generally believed by the ruling body that proprietorship could be freely transformed without any negative consequences.